A Study of Nanofluid Flow with Free Bio-Convection in 3D Nearby Stagnation Point by Hermite Wavelet Technique - Raghunatha, K. R.; Kumbinarasaiah, S.; İnç, Mustafa; Akgul, Ali (Amer Scientific Publishers, 2024)
A new wavelet-numerical method for solving a system of partial differential equations describing an incompressible bio-convection nanofluid flow in a three-dimensional region close to the stagnation point is the primary focus of this article. Hermite wavelets form the basis of the algorithm. An assortment of similitude factors is utilized to improve on the overseeing conditions addressing the protection of all out mass, force, nuclear power, nanoparticles, and microorganisms to a bunch of completely connected nonlinear common differential conditions. The most important physical quantities that have a practical impact on the spread of motile bacteria are presented and analyzed in this paper. During bio-convection, the Prandtl, Lewis, Peclet, Schmidt, and Rayleigh numbers can alter the distribution of moving molecules. The dispersion of microorganisms can be emphatically affected by the kinds of nanoparticles and by the varietis in the temperature as well as volumetric part of the IP: 203.8.109.20 On: Tue, 16 Apr 2024 14:56:17 nanoparticles between the wall and the encompassing liquid. With excellent agreement for coupled nonlinear differential equations in engineering applications, our result demonstrates how powerful and simple the HWM Delivered by Ingenta is for solving these coupled nonlinear ordinary differential equations.
Keywords: Hermite Wavelets; Nonlinear Differential Equations; Operational Matrix of Integration; Collocation Method; Bio-Convection; Nanofluid